186 RARE CASE OF A GIANT THYMIC CYST: A CHALLENGING DIFFERENTIAL DIAGNOSIS OF A PARACARDIAC CYSTIC LESION. (15th December 2022) - Schiavo, Maria Alessandra; Foroni, Marco; Coccolo, Fabio; Graziosi, Maddalena; Attinà, Domenico; Dolci, Giampiero; Galiè, Nazzareno
Abstract: Background: Benign thymic cysts are a rare clinical entity, representing approximately 3% of all mediastinal masses. Thymic cysts can be congenital or acquired. We describe a case of a 58-year-old female with a giant benign thymic cyst which entered in differential diagnosis with a pericardial cyst and pericardial effusion. Case presentation: A 58-year-old female was brought to our hospital due to new onset dyspnoea and fatigue. She had a history of a liquid mediastinal mass accidentally discovered 9 years before which was interpreted at that time as a loculated pericardial effusion (Fig. 1). An echocardiogram was performed which showed increased size of the known lesion without any signs of hemodynamic compromise (Fig. 2). A magnetic resonance showed a voluminous liquid lesion that originated from the anterior mediastinum, extending caudally to the diaphragm with maximum dimensions on the right hemithorax of 16×12×9 cm (antero-posteriorly, transversely and cranio-caudally respectively) and of 10×5×13 cm on the left hemithorax (Fig. 3). It was initially interpreted as a pericardial cyst. All the findings were then collegially reviewed and for the first time it was suspected of being a giant thymic cyst, especially due to its spatial distibution and growth over time; in particular the cranio-caudal growth in both the hemithoraxes suggested that it might have originated from the thymus gland and then, by force of gravity, extended downword bilaterally. The cyst was surgically removed using a unilateral thoracoscopic approach. Histological examination confirmed the thymic origin of the cyst and excluded malignancy. At the three month follow up, the patient presented no symptoms, and the echocardiogram was normal. Discussion: The echocardiographic features of mediastinal cysts are not lesion-specific, so the origin and location of the cyst can be used for differential diagnosis. Computed tomography has the best spatial resolution, while the magnetic resonance has better capacity to differentiate the content of the cyst, especially when it is not a homogeneous liquid lesion. In our case, spatial distribution and, in particular, growth over nine years were crucial hints to suspect the thymic origin of the lesion. Indeed, the sole evaluation of the last imaging exam would have made the diagnosis more problematic because of its huge dimensions, which made the exact site of origin very challenging to identify. Conclusion: Our case is a rare example of a giant thymic cyst which was extremely difficult to differentiate from other paracardiac cystic lesions and required integrated imaging and discussion by a team of experts of different specialties to make the correct diagnosis.